Sliding mode control for a wind turbine in finite frequency. (2018) - Berrada, Youssef; Boumhidi, Ismail
This paper investigates a sliding mode control for a wind turbine in finite frequency (FFSMC). The sliding mode control (SMC) method can be designed for wind energy conversion systems. However, the fluctuations of wind speed perhaps reduce the robustness of the SMC. A dynamic compensator is introduced to design the sliding surface in order to overcome the difficulty of dealing with a fluctuation of wind speed, but the fast change of this fluctuation in certain finite ranges can lead to degrade the compensator performance. In order to solve thisproblem, a finite frequency approach based on the generalised Kalman-Yakubovich-Popov (KYP) lemma is proposed, and the compensator parameters are obtained in terms of linear matrix inequality (LMI) which can be solved efficiently using existing numerical tools. On the other hand, the reaching law is used to reduce the chattering that is produced by the traditional approach of sliding mode. Finally, the simulation results illustrate the effectiveness of the proposed control strategy compared to a non-singular terminal sliding mode control.